The effect of the ratio of male to female Broodstock on the production of tilapia (Oreochromis niloticus) Seed - Herman, Azman; Malik, Andi Adam; Sahabuddin, Sahabuddin; Yushra, Yushra; Rusdi, Rismawaty (Universitas Malikussaleh, 2024)
This research was conducted from November to December 2023 at the Production Centre of Pangkajene Fish Seed Institute, Sidenreng Rappang Regency, South Sulawesi Province. The objective of this study was to determine the effect of the ratio of male and female broodstock on tilapia seed production, and to determine the ratio of male and female broodstock that produce the most seed production. The design used was a completely randomised design with 4 treatments and 3 replications. The data obtained were presented in the form of graphs and tables. The effect of treatment was analysed using analysis of variance (ANOVA) followed by Tukey's test. The results of the analysis showed that the ratio of male to female broodstock had a significant effect on tilapia fry production (P < 0.05) Sig = 0.034. The highest seed production was found in treatment C (1 male: 4 females) with an average production of 71,000 seeds. Treatment B (1 male: 3 females), 51,000 seeds, treatment D (1 male: 5 females), 34,000 seeds and treatment A (1 male: 1 female) with an average production of 21,000 seeds. It can be concluded that the ratio of male to female broodstock has a significant effect on the production of nila fish fry (Oreochromis niloticus). The highest fry production was obtained in the ratio 1 male; 4 females.Keywords: Broodstock; Production; Ratio; Seed; Tilapia